PRODUCT DEVELOPMENT OF BAKPIA MBAH WIRO 378 INDEPENDENCE COACHING BASED ON CREATIVE ECONOMY AT YOGYAKARTA CLASS IIA PRISON - Dimas Muhammad Rafi Fahrezy; Iman Santoso (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the development of the independence training program through the production of “Bakpia Mbah Wiro 378” at Lapas Class IIA Yogyakarta, which integrates creative economy principles into correctional vocational activities. The research focuses on examining how the product development process is implemented within the training program and identifying the challenges that hinder its optimization. The study employs a qualitative descriptive approach, with data collected through observation, structured interviews with key informants, literature review, and document analysis. The findings indicate that the bakpia production program contributes positively to improving inmates’ practical skills, work discipline, and entrepreneurial insight, which can support their social reintegration after release. Through participation in the production process, inmates gain experience in food processing, teamwork, and responsibility in a work environment. However, the program still faces several obstacles, such as limited access to quality raw materials, the lack of modern production equipment, limited marketing strategies, and restricted access to broader markets. Therefore, the study highlights the importance of product innovation, strengthening cooperation with government institutions and private partners, and utilizing digital platforms such as social media and e-commerce to expand market reach and improve the sustainability of correctional industry products. This research contributes to the discussion on creative economy-based correctional empowerment programs and provides recommendations to enhance the competitiveness and sustainability of products produced within correctional institutions. Keywords: Correctional Institution; Inmate Empowerment; Vocational Training; Creative Economy; Product Development; Reintegration